Time-restricted eating (TRE) for obesity in general practice: study protocol of a controlled, randomized implementation study (INDUCT) within the Research Practice Network Baden-Wuerttemberg (FoPraNet-BW) - Braun, Lorena; Haumann, Hannah; Polanc, Andreas; Koch, Roland; Feil, Elke; Klein, Anika; Höner, Claudia Johanna; Peters-Klimm, Frank; Hübner, Gudrun; Thies, Christian; Biergans, Stephanie; Joos, Stefanie (Nutrition journal, 2025)
Obesity is a major health problem with a significant impact on quality of life and is a major risk factor for other diseases such as diabetes. There is a growing body of evidence that time-restricted eating (TRE) as one form of intermittent fasting (IF) represents a promising weight management strategy. Given the lack of evidence-based weight management strategies in the primary health care setting, the aim of this study is to investigate the effect of TRE in general practice in Germany. INDUCT is a type hybrid I, randomized-controlled study conducted in 41 practices within the newly established general practice-based research network (GPBRN) in Baden-Wuerttemberg (FoPraNet-BW). The study population consists of patients with a Body Mass Index between 30-45 kg (kg)/m2. The intervention group receives TRE at the scheme 16:8 (16 h fasting; 8 h energy intake) while the control group receives care as usual. The primary outcome is change in body weight under a 6-month period of TRE. Secondary outcomes are related to the patient (e.g. quality of life) and the practice (e.g. knowledge about research in own practice). As the INDUCT study represents one of the first four use-cases within the Research Network Baden-Wuerttemberg (FoPraNet-BW), feasibility is a further secondary outcome. The target sample size is 208 patients with a 1:1 randomization. An intention-to-treat approach is used for data analysis. INDUCT adds evidence on the effect of TRE as a weight management strategy in general practice. Relevant factors for a sustainable and successful implementation in general practice will be revealed and can be applied for future implementation of TRE interventions in general practice if proven successful. In addition, important lessons learned regarding the conduction of clinical research within FoPraNet-BW will be derived. This fosters a sustainable implementation of a research infrastructure in general practice in Germany. DRKS-ID (German Clinical Trials Register-ID): DRKS00031928 (Date of registration in DRKS: 2023-06-22; Link: https://drks.de/search/de/trial/DRKS00031928 ).